High-pressure measurements of mid-infrared electroluminescence from InAs light-emitting diodes at 3.3 μm - Choulis, Stelios A.; Andreev, Aleksey D.; Merrick, Michael L. (My University, 2003)
The spontaneous electroluminescence emission of InAs light-emitting diodes (LEDs) operating at 3.3 μm was studied as a function of applied hydrostatic pressure. An enhancement of a factor of almost four in radiative efficiency at room temperature was observed in the range 0 to 10 kbar. Analysis of the dependence of electroluminescence emission intensity on hydrostatic pressure at constant current reveals that nonradiative Auger recombination dominates the quantum efficiency of these LEDs
Keywords: Light emitting diodes; Electroluminescence; Indium compounds; Liquid phase epitaxy; Photolithography; Pressure--Measurement